INTEREST RATE PREDICTABILITY IN SOME SELECTED AFRICAN COUNTRIES - Bidias-Menik, Hans Patrick; Tonmo, Simplice Gaël (Copernican Journal of Finance & Accounting, 2021)
This study tries to verify the predictive power of the implicit forward rate of the term structure of interest rates in Africa. We used data from Egypt, Ghana, Kenya, Nigeria and the Republic of South Africa. A modified version of the yield term premium and the forward term premium models of Shiller and McCulloch (1990) were used to test the predictive power of the implicit forward rate, rather than the rational expectations hypothesis. We both used FMOLS and DOLS estimators, since they are more consistent than OLS with non-stationary series. The overall results show that the implicit forward rate does not have a significant predictive power in Africa. It therefore appears that operators on African markets should not rely on those predictions.